Wie die Wikinger das Nordmeer überqueren konnten - Hohmann, Sascha (Astronomie + Raumfahrt im Unterricht)

Wortkritik als Aufgabenfeld einer diversitätssensiblen Literaturdidaktik. Das Verfahren der Dechiffrierung als ein Weg fachintegrativer Verankerung von Diversitätssensibilität - Kißling, Magdalena (Diversitätsorientierte Deutschdidaktik: Theoretisch-konzeptionelle Fundierung und Perspektiven für empirisches Arbeiten. Band 4 SLLD (B))
Keywords: Diversität; Inklusion; Gender; Deutschdidaktik

‚Nofretete-Mädchen‘ als Aufstörende des Adipositas-Mythos. Interkulturelle Perspektive auf Adoleszenz am Beispiel von Stefanie Höflers Tanz der Tiefseequalle - Kißling, Magdalena (Adoleszenz und Alterität. Synergien aktueller Ansätze der interkulturellen Literaturwissenschaft und -didaktik)

Postkolonialismus. Der Deutschunterricht (5) LXXIV

Politik&Co. Wirtschaft-Politik 9/10, Gymnasium Nordrhein-Westfalen - Dieckmann, Eva; Kißling, Magdalena; Labusch, Alexandra; Lindner, Nora; Mertens, Julia; Rohde, Marius

Eine kulinarische Geschlechterordnung? Die Polarisierung von Geschlecht im Kontext medialer Inszenierung und alltagsweltlicher Darstellungen des Kulinarischen - Eremin, Oxana (GENDER. Zeitschrift für Geschlecht, Kultur und Gesellschaft)

#FeministKitchen [Notes] - Eremin, Oxana (FKW//Zeitschrift für Geschlechterforschung und visuelle Kultur)

(K)Eine Frage des Wissens: Zum Verhältnis von Gender Studies & Wissenstransfer - Eremin, Oxana; Krämer, Anike; Mattei, Annalisa (Wissenstransfer als Aufgabe, Herausforderung und Chance kulturwissenschaftlicher Forschung.)

Foodwork: Schlaglichter auf das Themenfeld von Essen, Kochen und Geschlecht - Eremin, Oxana (Soziale Passagen. Journal für Empirie und Theorie Sozialer Arbeit)

Effects of strong fringing magnetic fields on turbulent thermal convection - Bhattacharya, Shashwat; Boeck, Thomas; Krasnov, Dmitry; Schumacher, Jörg (arXiv:2211.00559)
We study the influence of fringing magnetic fields on turbulent thermal convection in a horizontally extended rectangular domain. The magnetic field is created in the gap between two semi-infinite planar magnetic poles, with the convection layer located near the edge of the gap. We employ direct numerical simulations in this setup for fixed Rayleigh and small Prandtl numbers, but vary the fringe-width by controlling the gap between the magnetic poles and the convection cell. The magnetic field generated by the magnets is strong enough to cease the flow in high magnetic flux region of the convection cell. We observe that as the local vertical magnetic field strength increases, the large scale structures become thinner and align themselves perpendicular to the longitudinal sidewalls. We determine the local Nusselt and Reynolds numbers as functions of the local Hartmann number (based on the vertical component of the magnetic field) and estimate the global heat and momentum transport. We show that the global heat transport decreases with increasing fringe-width for strong magnetic fields but increases with increasing fringe-width for weak magnetic fields. In the regions of large vertical magnetic fields, the convective motion becomes confined to the vicinity of the sidewalls. The amplitudes of these wall modes show a non-monotonic dependence on the fringe-width.

Agnostic Explanation of Model Change based on Feature Importance - Muschalik, Maximilian; Fumagalli, Fabian; Hammer, Barbara; Hüllermeier, Eyke (KI - Künstliche Intelligenz)
Abstract Explainable Artificial Intelligence (XAI) has mainly focused on static learning tasks so far. In this paper, we consider XAI in the context of online learning in dynamic environments, such as learning from real-time data streams, where models are learned incrementally and continuously adapted over the course of time. More specifically, we motivate the problem of explaining model change , i.e. explaining the difference between models before and after adaptation, instead of the models themselves. In this regard, we provide the first efficient model-agnostic approach to dynamically detecting, quantifying, and explaining significant model changes. Our approach is based on an adaptation of the well-known Permutation Feature Importance (PFI) measure. It includes two hyperparameters that control the sensitivity and directly influence explanation frequency, so that a human user can adjust the method to individual requirements and application needs. We assess and validate our method’s efficacy on illustrative synthetic data streams with three popular model classes.
Keywords: Artificial Intelligence

VALIDATION AND COMPARISON OF FEM-SIMULATION RESULTS OF THE FUSED DEPOSITION MODELING PROCESS UNDER CONSIDERATION OF DIFFERENT MESH RESOLUTIONS - Moritzer, Elmar; Hecker, Felix (Proceedings of the 33rd Annual Freeform Fabrication Symposium)

New York als Material - Künstlerische Forschung im Spannungsfeld von Kunstgeschichte, Kunstpraxis und Vermittlung - Autsch, Sabiene (Kunstpädagogik und ... Bezugsfelder und Perspektiven kunstpädagogischer Theorie und Praxis)

Die ASK und ihre Ausstellungen. Ein Visual Essay - Autsch, Sabiene; Pickartz, Tim (Bis hierhin und weiter. Hundert Jahre Arbeitsgemeinschaft Siegerländer Künstlerinnen und Künstler [= Publikation anlässlich der gleichnamigen Ausstellung, Städtische Galerie Haus See, Siegen, 29. Mai - 03. Juli 2022])

Mikroformen - Autsch, Sabiene (Lexikon der Kunstpädagogik)

Elegische Liebestragödie. Johann Elias Schlegels "Die Trojanerinnen" (1737/47) - Puscher, Sahra (ZwischenSpielZeit. Das Theater der Frühaufklärung (1680-1730))

Erkenntnisse zur Verbesserung von Mentoringprozessen in der Lehrer:innenausbildung - Goller, Michael; Caruso, Carina; Harteis, Christian (SEMINAR – Lehrerbildung und Schule)

Möglichkeiten und Grenzen der Messung, Kontrolle und Sicherung der Qualität logistischer Prozesse - Hrnjadovic, Damir (Aktuelle Fragestellungen zu Produktion, Logistik und Controlling)

Implikationen einer wertorientierten Unternehmensführung für Standortplanungsentscheidungen - Fiedler, Moritz (Aktuelle Fragestellungen zu Produktion, Logistik und Controlling)

Betriebliche Standortplanung international agierender Unternehmen - Osthoff, Lennart (Aktuelle Fragestellungen zu Produktion, Logistik und Controlling)